COVID‐19 infection in pediatric solid organ transplant patients. (11th October 2021) - Bansal, Neha; Ovchinsky, Nadia; Foca, Marc; Lamour, Jacqueline M.; Kogan‐Liberman, Debora; Hsu, Daphne T.; Beddows, Kimberly; Abraham, Lincy; Coburn, Maura; Cunningham, Ryan; Nguyen, Trang; Hayde, Nicole
Abstract: Background: Adult SOT recipients with COVID‐19 have higher mortality rates when compared to general population. There is paucity of data on outcomes in pediatric SOT recipients. Methods: This is a cross‐sectional study investigating the prevalence of COVID‐19 infection and outcomes in pediatric SOT (heart, liver, and kidney) recipients. We extracted demographic and clinical characteristics and COVID‐19 testing (PCR or [Ab] test) results from medical records. Clinical characteristics were compared between patients who were positive for COVID‐19 (PCR or Ab) and those who did not, using Mann‐Whitney, Student's t test, or chi‐square test. p value <.05 was statistically significant. Results: A total of 108 SOT recipients with a median age of 13.1 (8.4, 17.8) years and median 4.2 (2.7, 7.9) years from transplant were checked for COVID‐19 via a PCR or Ab test. A positive PCR was confirmed in 10 patients (9.3%), while 12 patients (11.1%) were positive for COVID‐19 Ab. The patients who tested positive in our cohort were 9/50 (18%) heart, 6/68 (8.8%) kidney, and 7/50 (14%) liver transplant recipients. There were no differences in the clinical characteristics between patients with and without COVID‐19 infection. All patients were either asymptomatic (50%) or had self‐limiting symptoms. No changes were made to the immunosuppressive regimen. Only one patient was hospitalized and none had an oxygen requirement. Conclusions: In our cohort of pediatric SOT recipients, COVID‐19 infection was asymptomatic or mild. This data may aid clinicians in counseling patients and families in this increased‐risk population.